Integrated generation-transmission expansion planning considering power system reliability and optimal maintenance activities - Mahdavi, Meisam [UNESP]; Javadi, Mohammad S.; Catalão, João P.S. (Elsevier, 2023)
This paper evaluates lines repair and maintenance impacts on generation-transmission expansion planning (GTEP), considering the transmission and generation reliability. The objective is to form a balance between the transmission and generation expansion and operational costs and reliability, as well as lines repair and maintenance costs. For this purpose, the transmission system reliability is represented by the value of loss of load (LOL) and load shedding owing to line outages, and generation reliability is formulated by the LOL and load shedding indices because of transmission congestion and outage of generating units. The implementation results of the model on the IEEE RTS show that including line repair and maintenance as well as line loading in GTEP leads to optimal generation and transmission plans and significant savings in expansion and operational costs.
Keywords: Generation and transmission reliability; Lines loading; Maintenance; Power-system expansion planning; Repair